Analisis Faktor- Faktor Yang Mempengaruhi Pengambilan Keputusan Lindung Nilai (Hedging) Menggunakan Instrumen Derivatif (Studi Kasus Pada Perusahaan Manufaktur Dan Perusahaan Energi Dan Sumber Daya Mineral Yang Terdaftar Di Bei Periode 2010-2014) - Mediana, Ima; Muharam, Harjum (Diponegoro Journal of Management, 2016)
Hedging is an alternative of risk management that aims to protect the assets of company from losses caused by the risk. This study’s purpose is to analyze the influence of leverage, liquidity, growth opportunity, financial distress, cash flow volatility and dummy variable for the different effect of mining companies to manufacturing companies on hedging decision using derivative instruments at  manufacturing and mining companies listed on the Indonesia Stock Exchange in 2010-2014. This study uses secondary data derived from 72 annual financial statements. Sampling using purposive sampling method with the provision of the company that publishes  financial statements. Data analysis using logistic regression test. The results of this study found that liquidity, growth opportunity, financial distress, and cash flow volatility have significant effect on Hedging Decision using derivative instruments, whereas for the other variables did not influence hedging decision using derivative instruments. From the results of logistic regression found that the variable leverage, liquidity, the growth opportunity, financial distress, cash flow volatility and dummy variable for the different effect of mining companies to manufacturing companies can explain Hedging Decision using derivative instruments  by 25,8%, and the rest is explained by other variables outside the model.